MESIN MINUMAN KOPI OTOMATIS BERBASIS IOT - Rafli Pratama; Ramadona; Zanu Saputra; Parulian Silalahi (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Coffee is the most popular drink for Indonesian people, both young and old. However, due to their busy schedules, they do not have time to make coffee. Therefore, we need a machine that can make coffee drinks without the need to make it manually. In this manufacture, it is proposed to make this Machine with the aim that the machine can be used as a business medium that can be controlled and monitored via a smartphone. The method of making this IoT-Based Automatic Coffee Beverage Machine uses Arduino Mega as a control system with push button input and an LCD display that will be used as a menu display. Then this machine is also equipped with a DS18B20 temperature sensor as a coffee drink temperature detection, an Ultrasonic sensor as a coffee capacity detector in the glass with the addition of an ordering and monitoring system using a smartphone. Based on the results of the tests carried out, data were obtained by conducting 8 experiments with 4 different doses. In testing the filling of coffee drinks with 4 experiments using the Button and in testing the filling of coffee drinks with 4 experiments using the application. From all the experiments carried out, it was found that the average percentage error of each dose of drink made was 1/4 cup with an error of 0.154%, 1/2 cup with an error of 0.032%, 3/4 cup with an error of 0.032% and 1 cup with an error of 0. 0.0268%. In the experiment of making coffee drinks to be stable starting from a drink temperature of 30º which is then heated with a temperature increase of 3-5ºC every minute and it only takes 6 minutes for the heater to reach the maximum temperature of 70ºC from coffee drinks. After that the heater will turn off and the temperature increase will decrease to 3-1ºC and the temperature of the coffee drink will be stable between 70-80ºC.